To trust or not to trust? Young people's trust in climate change science and implications for climate change engagement. Issue 3 (4th May 2021) - Ojala, Maria
ABSTRACT: This article discusses young people's trust or distrust in climate change science. The aim is to show how the emotional dimension of trust in climate change science plays a role for an engagement at two levels: how young people relate to climate change at large, if they worry or deny climate change, and how young people deal with ambivalence regarding behavioral advice about, for example, climate-friendly food choices. The article ends by elaborating on the need for more research about what role trust/distrust in climate change science plays in young people's everyday climate engagement, meaning-making, and identity development.